ACMEOLOGICAL APPROACH TO THE DEVELOPMENT OF PEDAGOGICAL PROFESSIONALISM (CAHIERS MAGELLANES-NS, 2024)
In the current globalization, the problem of teacher professionalism is becoming one of the most pressing issues. In order to develop the professionalism of each person in professional activity, it is important to preserve the inner "I" that can be the basis for self-analysis and understanding of his individual characteristics.Pedagogical professionalism is mainly determined by objective and subjective determinants of professional development. Because these determinants are a decisive factor in the development of pedagogue professionalism, ignorance of them leads to the development and implementation of wrong strategies for the development of pedagogue professionalism. This can lead to a one-sided development of the personality of the students they are teaching, as well as a psychological and physiological overload on the pedagogue.Our observations aimed at studying the process of developing teacher professionalism showed that there are a number of problems in this area. For example: